Pengaruh Komitmen Organisasional, Lingkungan Kerja, dan Stres Kerja Terhadap Turnover Intention Penelitian - Ardianus Gordi Pago; Prayekti Prayekti; Didik Subiyanto (Indonesian Journal of Multidisciplinary on Social and Technology, 2025)
Human Resources (HR) play a crucial role in an organization, impacting its performance and success. Strategic HR management is essential for optimal employee placement, development, and utilization, enabling organizations to harness human resources for achieving company goals. This study analyzes the relationship between organizational commitment, work stress, and the work environment concerning Turnover Intention. Researchers aim to understand how organizational commitment levels, job stress, and work environment quality contribute to employees' inclination to leave. Using a quantitative approach, data collection involved distributing questionnaires to 100 respondents. Analysis using the SPSS program provided deeper insights into the relationship between organizational commitment, work stress, and the work environment in the context of Turnover Intention. Findings indicate that organizational commitment (KO) lacks a significant effect on job change intention (IT). Work stress (SK) shows a positive but nonsignificant impact on intention to move, while the work environment (LK) has a positive and significant effect on changing job intentions. The study suggests that attention to organizational commitment, work stress, and work environment can potentially reduce job change desires. These insights guide management in developing strategies to enhance employee well-being and retention, contributing to organizational stability.